1997
DOI: 10.1002/(sici)1098-2795(199706)47:2<222::aid-mrd14>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin B1 expression in meiotically competent and incompetent goat oocytes

Abstract: To start determining the nature of meiotic incompetence in goat oocytes, we have examined the expression of one of the potential pre‐MPF subunits: the cyclin B1. We have been isolating a small DNA probe encoding the goat cyclin B1 box to analyze the expression of the cyclin B1 gene in competent and incompetent goat oocytes. This probe was easily obtained by polymerase‐chain‐reaction (PCR) on reverse‐transcribed mRNA from granulosa cells, using cyclin B specific primers derived from a bovine cDNA. The transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…Similar results were obtained from analysis of cyclin B mRNA transcripts (Fig. 1B), which would be expected to persist in the oocyte cytoplasm (Hue et al 1997). Interestingly, the oocytes used in these studies were obtained from a commercial dam line of pure white pigs.…”
Section: Resultssupporting
confidence: 75%
“…Similar results were obtained from analysis of cyclin B mRNA transcripts (Fig. 1B), which would be expected to persist in the oocyte cytoplasm (Hue et al 1997). Interestingly, the oocytes used in these studies were obtained from a commercial dam line of pure white pigs.…”
Section: Resultssupporting
confidence: 75%
“…The pelleted RNA was washed in 70% ethanol and dried prior to reverse transcription. First-strand cDNA was synthesized using a SuperScript Preamplification System for First Strand cDNA Synthesis kit (Life Technologies) and 100 ng of oligo(dT) [12][13][14][15][16][17][18] primer in a total reaction volume of 20 l. A cDNA aliquot of 2 l was subjected to quantitative polymerase chain reaction (PCR) amplification using a Light Cycler apparatus (Roche Diagnostics, Laval, PQ, Canada). Products were detected with SYBR Green (Roche Diagnostics).…”
Section: Quantitative Real-time Polymerse Chain Reactionmentioning
confidence: 99%
“…In the mouse, the acquisition of meiotic competence is partly associated with the synthesis of p34 cdc2 [14][15][16][17], suggesting that a lack of one of the MPF components keeps the oocyte in meiotic arrest. Similarly, although both cyclin B1 mRNA and protein have been detected in meiotically competent and incompetent goat oocytes [18], only p34 cdc2 mRNA is present in meiotically incompetent oocytes [19]. In contrast, both components of MPF are present in the pig oocytes, suggesting that meiotic arrest in the pig is likely controlled by another pathway that involves protein phosphate transfer (kinase and/or phosphatase) [20].…”
Section: Introductionmentioning
confidence: 99%
“…MPF activity appears just before germinal vesicle breakdown (GVBD) increasing until metaphase I; its activity is decreased in anaphase-telophase while its maximum level is reached at metaphase II (MII). It has been shown that incompetent goat oocytes have a limited amount of cyclin B1 (Hue et al 1997) and p34 cdc2 . MPF activity in calf and lamb oocytes were significantly lower than in cow and ewe oocytes (Ledda et al 2001, Salamone et al 2001, whereas (Han et al 2010) showed in mice that the MPF activity of prepubertal oocytes was significantly higher than that of adult oocytes.…”
Section: Introductionmentioning
confidence: 99%